2022
DOI: 10.1021/acs.jcim.2c00705
|View full text |Cite
|
Sign up to set email alerts
|

MILCDock: Machine Learning Enhanced Consensus Docking for Virtual Screening in Drug Discovery

Abstract: Molecular docking tools are regularly used to computationally identify new molecules in virtual screening for drug discovery. However, docking tools suffer from inaccurate scoring functions with widely varying performance on different proteins. To enable more accurate ranking of active over inactive ligands in virtual screening, we created a machine learning consensus docking tool, MILCDock, that uses predictions from five traditional molecular docking tools to predict the probability a ligand binds to a prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…Accurate prediction of protein-ligand binding affinity remains one of the grand challenges of computational chemistry and biology. [1][2][3] With the ever increasing amount of high-resolution experimentally determined protein-ligand structures, 4 the binding affinity prediction methods have switched from physicsbased [5][6][7][8][9][10][11] to empirical scoring functions [12][13][14][15] and knowledgebased, 16,17 and in the last decade to machine learning [18][19][20][21][22][23][24][25][26][27] and deep learning based methods. [28][29][30][31][32][33][34][35][36][37][38] Especially, deep learning is an end-to-end method that is ideally suited to find hidden nonlinear relationships 39 between 3D protein-ligand complex structures and binding affinity.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate prediction of protein-ligand binding affinity remains one of the grand challenges of computational chemistry and biology. [1][2][3] With the ever increasing amount of high-resolution experimentally determined protein-ligand structures, 4 the binding affinity prediction methods have switched from physicsbased [5][6][7][8][9][10][11] to empirical scoring functions [12][13][14][15] and knowledgebased, 16,17 and in the last decade to machine learning [18][19][20][21][22][23][24][25][26][27] and deep learning based methods. [28][29][30][31][32][33][34][35][36][37][38] Especially, deep learning is an end-to-end method that is ideally suited to find hidden nonlinear relationships 39 between 3D protein-ligand complex structures and binding affinity.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the library size increases, so does the number of potential artifacts, 24 calling for the development of novel automated ways to limit human intervention. One of the proposed strategies is to select molecules that showed consensus results across multiple docking programs with the aim to counterbalance overestimations of individual scoring functions 24,26,108,109 . For example, a consensus strategy adopted in our recent DD screen of a multi‐billion library composed of REAL Space and ZINC15 against the nontrivial Mpro target allowed to achieve significantly high hit rates, especially when paired with expert hit selection 41 .…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…One of the proposed strategies is to select molecules that showed consensus results across multiple docking programs with the aim to counterbalance overestimations of individual scoring functions. 24,26,108,109 For example, a consensus strategy adopted in our recent DD screen of a multi-billion library composed of REAL Space and ZINC15 against the nontrivial Mpro target allowed to achieve significantly high hit rates, especially when paired with expert hit selection. 41 Lyu et al proposed to select candidates for experimental validation also from lower scoring bins because they observed that artifact molecules may be heavily concentrated at the top of the docking rank.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…A brief overview of this has been provided in a review of molecular docking written by Torres et al 11 Some of the most recent consensus docking publications include DockECR 17 and MILCDock. 18 Palacio-Rodri ́guez et al described an exponential consensus ranking (ECR) method that uses an exponential distribution for each individual rank of every docking method. 19 Their method is implemented in such a way that compounds which score very well in a single method can still be ranked highly even though they score worse in the other docking methods.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A brief overview of this has been provided in a review of molecular docking written by Torres et al . Some of the most recent consensus docking publications include DockECR and MILCDock . Palacio-Rodríguez et al.…”
Section: Introductionmentioning
confidence: 99%